Minors contracts: its legal and equitable effects / Amir Abd. Aziz - Abd. Aziz, Amir (Faculty of Law, 1986)
The objective of this project paper is to look into the agreements made by minors whose contractual capacity has long been considered a controversial mattero Now the capacity of minors to contract has been fixed at 18 and this reduction from 21 was mainly due to the interferences of legislative bodies in introducing measures to make an agreement in which a minor is one of the parties, more equitable between the parties. But issues which are questionable and disputable still arise from the agreements made by those under 18. This matter needs to be scrutinised espacially when it is concerned with the division of powers and rights of the contracting parties. Therefore in discussing that area, the writer will focus on the legal and equitable effects of such agreements.The discussion will be made by looking at the position under the Contracts Act, 1950 with references to be made to English Common Law and Indian authorities, which are applicable. The introduction of an Amendment Act, 1976 of the Contracts Act, 1950 with regard to scholarship agreements entered into by minors has brought about some significances in its nature. By its strict application, the distinct changes in it haveled the creation of a notion of unequal bargaining of power between the contracting parties. this notion is concerned with the